Figs: An ocean of nutrients - YADAV, KALPANA; Kapil; Yogita (Indian Horticulture, 2022)
Figs have been consumed by humans since ancient times. Figs are eaten in fresh and dried form; however, since fresh figs are highly perishable, they are mainly consumed near production areas. Thus, most figs are consumed in the form of dried fruits, which are a concentrated source of nutrients. They are an excellent source of fibre, potassium, calcium, iron and many other nutrients. A single serving of figs contains 20% of the daily intake of dietary fibre, which makes them a useful snack item for a variety of individuals and aids in digestion. Figs are a rich source of a wide range of phytochemicals with health-promoting properties and also serve as a therapy for a variety of conditions.